Synthesis of matrix-free blue-green dual-color solid-state fluorescent carbon dots and their applications in LED and fingerprint detection

By synthesizing blue-ray seed carbon dots with 1,2,4-benzenetriacetic acid and urea, and preparing green and strong blue-ray carbon dots through oxidation and NaOH treatment, the problem of multi-color solid carbon dot synthesis is solved, and efficient and low-cost multi-color fluorescent material preparation is achieved, suitable for LED and fingerprint detection.

CN119432374BActive Publication Date: 2025-04-25YUXI NORMAL UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411570845.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-04-25
Estimated Expiration
2044-11-06

AI Technical Summary

Technical Problem

It is difficult to prepare matrix-free multicolor solid carbon spots with anti-aggregation-induced quenching effect, and traditional fluorescent materials have problems of heavy metal contamination and high cost.

Method used

By using 1,2,4-benzenetriacetic acid and urea as precursors, blue-ray seed carbon dots were synthesized by microwave-assisted method, and then green and strong blue-ray carbon dots were prepared by H2O2 oxidation and NaOH treatment, respectively, and the synthesis of multi-color solid carbon dots was achieved.

Benefits of technology

The prepared carbon dots have high quantum yield, good light stability and photobleaching resistance, low cost and simple synthesis method, and are suitable for LED lighting and fingerprint detection and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119432374B_ABST
    Figure CN119432374B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of nano-synthetic materials, discloses a method for synthesizing matrix-free blue-green dual-color solid fluorescent carbon dots and their applications in LED and fingerprint detection, synthesizes blue light seed carbon dots (S-CDs) by 1,2,4-benzenetricarboxylic acid and urea, and successfully prepares green light (G-CDs) and strong blue light carbon dots (B-CDs) with quantum yields increased by 35 times and 75 times, respectively, by H2O2 oxidation and NaOH treatment. The study reveals the regulatory effects of quantum size effect and surface state change on fluorescence color and quantum yield, wherein hydrogen peroxide and sodium hydroxide treatment improve the photoluminescence performance of CDs by changing surface groups and destroying hydrogen bonds. The synthesized G-CDs and B-CDs have the advantages of strong fluorescence, photobleaching resistance, good photostability, low cost and simple synthesis, and are combined with commercial red phosphors to prepare white light LEDs with high color rendering index and suitable color temperature, which are suitable for indoor lighting. In addition, B-CDs and G-CDs, as fluorescent markers, can effectively improve the accuracy and reliability of latent fingerprint detection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nanomaterials, and relates to a method for synthesizing matrix-free blue-green dual-color solid-state fluorescent carbon dots and applications thereof in LED and fingerprint detection. Background Art

[0002] At present, white light emitting diodes (WLEDs) are considered to be ideal lighting devices due to their high reliability, long life, small size, short response time, high light efficiency and low energy consumption. It is worth noting that the development of electronic products today leads to eye fatigue. W-LEDs with high color rendering index (CRI) and low color temperature can effectively reduce eye fatigue because of their comfortable light emission close to the ideal light source (sunlight). In recent years, WLEDs have been widely used in production and life. Semiconductor quantum dots and rare earth materials are commonly used commercial phosphors. Semiconductor quantum dots have high photoluminescence quantum yield (PLQY) and narrow full width at half maximum (FWHM), but heavy metals such as lead, cadmium and indium are potentially toxic, and rare earth materials are non-renewable and expensive. Therefore, it is very important to develop multicolor fluorescent materials with excellent fluorescence properties, good stability, low cost, low toxicity and simple synthesis methods.

[0003] Fingerprints are used as one of the important means of personal identification due to their specificity and stability. When fingers touch the surface of an object, sweat and oily secretions will form fingerprints that are invisible to the naked eye and are usually called latent fingerprints (LFP). Fingerprint enhancement technology refers to the use of markers such as ninhydrin, iodine treatment, cyanoacrylate fumigation, black powder dust, silver nitrate, etc. to make LFP visible. Latent fingerprint detection in criminal cases can be used as important evidence to solve the case. Therefore, the development of new fluorescent markers is of great practical significance for fingerprint enhancement technology.

[0004] Carbon dots (CDs) are a new type of zero-dimensional carbon nanomaterials, whose size is usually less than 10 nanometers. A large number of studies have shown that CDs are composed of sp 2 / sp 3 CDs are composed of a carbon core and various surface functional groups. Currently, CDs are widely used in bioimaging, chemical sensors, fluorescent probes, information anti-counterfeiting and LEDs. CDs show great potential as WLED conversion layers and potential fingerprint fluorescent markers due to their high quantum yield (QY), tunable fluorescence emission, good optical stability, small particle size and simple synthesis methods.

[0005] To date, many synthetic strategies have been explored to prepare color-tunable multicolor fluorescent carbon dots, such as by changing the reaction temperature, reaction time, solvent type or reactant ratio. Nevertheless, the preparation of matrix-free multicolor solid-state CDs with resistance to aggregation-induced quenching remains a challenge. There are few reports on the treatment of seed carbon dots with oxidants and strong bases to achieve tunable fluorescence emission and multicolor solid-state carbon dots with greatly improved quantum yield. Therefore, it is of great significance to establish a simple, fast, mild and low-cost method to synthesize efficient multicolor solid-state CDs. Summary of the invention

[0006] The present invention aims to synthesize blue light seed carbon dots (S-CDs) by using 1,2,4-benzenetricarboxylic acid and urea as precursors. Subsequently, green light carbon dots (G-CDs) and strong blue light carbon dots (B-CDs) are prepared respectively by H2O2 oxidation and NaOH treatment. These carbon dots have high quantum yield, good photostability and resistance to photobleaching, low cost and simple synthesis method.

[0007] The technical solution of the present invention is

[0008] In a first aspect, the present invention provides a method for synthesizing matrix-free blue-green dual-color solid-state fluorescent carbon dots, comprising the following steps:

[0009] 1) Using 1,2,4-benzenetricarboxylic acid and urea as precursors, a microwave-assisted method was used to synthesize blue light-seeded carbon dots S-CDs;

[0010] 2) The synthesized S-CDs were oxidized with 3% H2O2 to obtain green light carbon dots G-CDs;

[0011] 3) Treat G-CDs with 0.1 mol / L NaOH to obtain strong blue light carbon dots B-CDs.

[0012] Preferably, the microwave-assisted synthesis condition is heating at medium-high power for 10 minutes.

[0013] Preferably, the H2O2 oxidation treatment and NaOH treatment time are both 12 hours.

[0014] In a second aspect, the present invention further provides an application of the carbon dots synthesized in the first aspect in LED lighting.

[0015] a) mixing the synthesized B-CDs and G-CDs with commercial red phosphor in a mass ratio of 2:3:1;

[0016] b) combining the mixed phosphor with a 365nm UV chip as a substrate to prepare a white light LED;

[0017] c) The white light LED has a color rendering index CRI of up to 91.4 and a correlated color temperature CCT of 5437K.

[0018] In a third aspect, an application of the carbon dots synthesized in the first aspect in latent fingerprint detection is provided, using the synthesized B-CDs and G-CDs as fluorescent markers to improve the accuracy and reliability of latent fingerprint detection.

[0019] In a fourth aspect, the present invention further provides a white light LED prepared by the method described in the second aspect, which has a high color rendering index and a suitable color temperature and is suitable for indoor lighting.

[0020] In a fifth aspect, the present invention provides a fluorescent marker prepared by the method of the fourth aspect, which is used to improve the accuracy and reliability of latent fingerprint detection.

[0021] In a sixth aspect, the present invention provides an application value of the B-CDs and G-CDs carbon dots obtained in the first aspect for biological imaging, chemical sensors, fluorescent probes and information anti-counterfeiting. Compared with the prior art, the present invention has the following advantages:

[0022] 1. Tunability of optical properties: Through simple and mild synthesis and post-treatment steps, the optical properties of carbon dots, including fluorescence color and quantum yield, can be tuned, providing flexibility for different applications.

[0023] 2. High quantum yield: Through specific synthesis and post-processing steps, the quantum yields of green light carbon dots (G-CDs) and strong blue light carbon dots (B-CDs) obtained are increased by 35 times and 75 times respectively compared with the original blue light seed carbon dots (S-CDs).

[0024] 3. Photostability: The synthesized carbon dots exhibit good photostability, which means that they can maintain their fluorescence properties under continuous illumination and are suitable for long-term applications.

[0025] 4. Photobleaching resistance: Carbon dots have good photobleaching resistance and will not fade even under long-term light exposure, which is crucial for their applications in LED lighting and fingerprint detection.

[0026] 5. Cost-effectiveness: The synthesis method is simple and the precursors and processing agents used are low-cost, making large-scale production possible while maintaining cost-effectiveness.

[0027] 6. Environmentally friendly: No toxic heavy metals are used in the synthesis process, reducing the potential risks to the environment and human health.

[0028] 7. White light LED with high color rendering index: Combined with commercial red phosphor, the white light LED produced has a high color rendering index (CRI up to 91.4), providing a more natural and comfortable lighting environment, suitable for indoor lighting.

[0029] 8. Improve fingerprint detection: As fluorescent markers, B-CDs and G-CDs can effectively improve the accuracy and reliability of latent fingerprint detection, which is of great significance in the fields of forensics and security.

[0030] 9. Simple synthesis method: The synthesis process is simple and easy to operate, which facilitates rapid production and application.

[0031] 10. Wide application potential: In addition to their applications in LED lighting and fingerprint detection, these carbon dots may also show potential application value in the fields of bio-imaging, chemical sensors, fluorescent probes, information anti-counterfeiting, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0033] Figure 1 Schematic diagram of the preparation process and application of S-CDs, G-CDs and B-CDs of the present application;

[0034] Figure 2 TEM images and particle size distributions of (a, d) S-CDs, (b, e) G-CDs, and (c, f) B-CDs of this application (the insets are HR-TEM images);

[0035] Figure 3 XRD images of three carbon dots in this application;

[0036] Figure 4 X-ray photoelectron spectra of (a) S-CDs, (b) G-CDs, (c) B-CDs and high-resolution spectral fitting analysis of C1s, N 1s and O1s elements corresponding to the three carbon dots of this application;

[0037] Figure 5 FT-IR spectra of three carbon dots in this application;

[0038] Figure 6UV-visible absorption spectra (black line), FL excitation spectra (red line) and emission spectra (blue line) of aqueous solutions of (a) S-CDs, (b) G-CDs and (c) B-CDs of the present application (the inset shows the corresponding photos of the three carbon dots under sunlight and UV lamp (365nm)); (df) FL emission spectra of the three carbon dot aqueous solutions at different excitation wavelengths;

[0039] Figure 7 This is a graph of the absolute fluorescence quantum yield of liquid state of S-CDs prepared in this application;

[0040] Figure 8 This is a graph of the absolute fluorescence quantum yield of liquid G-CDs prepared in this application;

[0041] Fig. 9 This is a diagram of the absolute fluorescence quantum yield of liquid state of the prepared B-CDs of this application;

[0042] Fig.10 UV-visible absorption spectra (black line), FL excitation spectra (red line) and emission spectra (blue line) of (a) S-CDs, (b) G-CDs and (c) B-CDs solid powders of the present application (the inset shows the corresponding photos of the three carbon dots under sunlight and UV lamp (365nm)); (df) FL emission spectra of the three carbon dot solid powders at different excitation wavelengths;

[0043] Fig.11 The photostability data of (a) G-CDs and (b) B-CDs of the present application under continuous irradiation with UV light (365 nm) for 1 hour;

[0044] Fig.12 The luminous spectra and physical pictures (illustrations) of (a) B-LED, (b) G-LED and (c) warm white light optoelectronic device (W-LED) of the present application; (d) CIE coordinate diagram corresponding to the luminous spectra of B-LED, G-LED and W-LED;

[0045] Fig.13 The following are (a) a latent fingerprint imaging photograph on a black cardboard with G-CDs powder as a fluorescent marker; (b) a latent fingerprint imaging photograph on a tin foil with B-CDs powder as a fluorescent marker; DETAILED DESCRIPTION

[0046] In the following description, specific details such as specific system structures, technologies, etc. are provided for the purpose of illustration rather than limitation, so as to provide a thorough understanding of the embodiments of the present application. However, it should be clear to those skilled in the art that the present application may also be implemented in other embodiments without these specific details. In other cases, detailed descriptions of well-known systems, devices, circuits, and methods are omitted to prevent unnecessary details from obstructing the description of the present application.

[0047] 1. Experimental drugs and instruments

[0048] 1.1 Experimental drugs

[0049] 1,2,4-Benzenetricarboxylic acid, urea, 3% H2O2, 0.1mol / LNaOH, and the water used in this experiment was distilled water.

[0050] 1.2 Experimental instruments

[0051] Table 1 Experimental instruments

[0052]

[0053] 2. Carbon Dots Preparation

[0054] Preparation of three kinds of CDs: Disperse 0.5253g of 1,2,4-benzenetricarboxylic acid and 0.7525g of urea in 7mL of deionized water, stir until evenly dispersed, and heat in a microwave oven at medium-high power for 10 minutes. After the reaction is completed, wait for it to cool to room temperature. Grind it with an agate mortar, add 20mL of deionized water and ultrasonicate for 5 minutes, filter it with a 0.22μm microporous filter membrane, transfer the filtrate to a 1000Da dialysis membrane and dialyze it for 24 hours (change the water every 6 hours), and dry it at 60°C for 12 hours to obtain a white powder, which is the seed carbon dots (S-CDs) that emit blue fluorescence. Place 1g of S-CDs in a beaker and use 10mL of 3% H2O 2浸 Soak for 12 hours and dry at 60°C to obtain a milky white powder as green fluorescent carbon dots (G-CDs). Soak the synthesized G-CD in 0.1M sodium hydroxide for 12 hours and then dry at 60°C to obtain a light yellow powder as strong blue fluorescent carbon dots (B-CDs). Figure 1 shown.

[0055] 3. Results and Discussion

[0056] 3.1 Morphology and structure

[0057] 3.1.1 TEM and XRD characterization

[0058] The morphologies of the three carbon dots were characterized using transmission electron microscopy (TEM). Figure 2As shown in the figure, the S-CDs, G-CDs and B-CDs samples are all spherical nanoparticles, which are evenly dispersed. There is no obvious aggregation phenomenon, and the average particle sizes are 31.55nm, 2.63nm and 2.01nm respectively. The sizes of the three are obviously different. There are a large number of hydrogen bonds between 1,2,4-benzenetricarboxylic acid and urea. During the microwave heating process, S-CDs are formed after cross-linking polymerization, dehydration and carbonization. After 3% H2O2 oxidation treatment, the surface functional groups of S-CDs are oxidized, and the hydrogen bonds of S-CDs may be destroyed at the same time, thereby forming G-CDs with a smaller particle size than S-CDs. The change in the surface state leads to a red shift in photoluminescence. The G-CDs prepared by further treatment with 0.1M NaOH may further destroy the hydrogen bonds, further reduce the particle size, and cause the photoluminescence (PL) to blue shift, forming B-CDs with a smaller particle size. High-resolution TEM (HR-TEM) images show that S-CDs, G-CDs and B-CDs all exhibit crystallinity, with lattice fringe spacings of 0.53nm, 0.245nm and 0.213nm, respectively, corresponding to the plane spacing of carbon materials, and the lattice spacing of G-CDs coincides with the (112) crystal plane of graphite carbon, and the lattice spacing of B-CDs corresponds to the (100) crystal plane of graphite carbon. In order to further understand the structural morphology of carbon dots, the structural crystalline state of CDs was analyzed by X-ray diffraction spectroscopy, such as Figure 3 As shown. The XRD diffraction peaks of S-CDs and G-CDs are similar, indicating that they have similar crystal structures, and both have sharp diffraction peaks around 27°, indicating that the interlayer spacing is 0.36nm, which may be caused by the residual -COOH at the edge. The XRD of B-CDs is a sharp peak with a narrow peak width, and there are many scattered sharp diffraction peaks at other positions, which shows that B-CDs have good crystallinity and rich surface groups.

[0059] 3.1.2 XPS characterization

[0060] XPS and FTIR were used to analyze the chemical composition and surface functional groups of the three CDs. Figure 4As shown in the figure, the proportion of C in S-CDs is 54.81%, N is 21.39%, and O is 23.8%. In G-CDs, the proportion of C and N is slightly decreased (C = 53.7%; N = 20.17%), and the content of O is significantly increased (O = 26.13%). The element content of B-CDs obtained after NaOH treatment has changed significantly, and Na element is also added. The proportions of C, N, O and Na elements are 37.21%, 2.62%, 41.29% and 18.89% respectively. The content of N element is significantly reduced. From the high-resolution spectrum of C1s, it can be seen that the surface groups of S-CDs and G-CDs are similar, both containing -COOH (289.16 eV), C=C / CC (284.79 eV), C=O / C=N (288.35 eV) and CO / CN (285.12 eV) structures. The surface groups of B-CDs are C=O / C=N (288.34 eV), CC (283.75 eV), C=C (284.75 eV) and CO / CN (287.32 eV), indicating that all three are composed of a large number of benzene ring skeletons and have a high degree of graphitization. According to the N1s high-resolution spectrum, S-CDs and G-CDs contain pyridinic nitrogen (398.9eV), pyrrolic nitrogen (400.21eV), and amino nitrogen (399.3eV), respectively; B-CDs contain amino nitrogen (399.74eV), pyridinic nitrogen (399.09eV), and sodium nitride (398.02eV). In the process of forming B-CDs, NaOH may destroy the hydrogen bonds and disperse the nitrogen-containing groups on the surface of the carbon core, resulting in a significant decrease in the N content and particle size in B-CDs, which is consistent with the results of TEM. The high-resolution spectrum of O1s shows that both S-CDs and G-CDs contain C=O (531.2 eV) and C-OH / COC (532.8 eV) structures; B-CDs contain C=O (530.8 eV), -COOR (535.29 eV) and sodium oxide (530.38 eV).

[0061] 3.1.3 Fourier transform infrared spectroscopy (FT-IR) characterization

[0062] like Figure 5 As shown, S-CDs and G-CDs have similar FT-IR spectra. -1 , 3325cm -1 and 3063cm -1 / 3030cm -1 The absorption peaks at 1764 cm-1 can be attributed to the stretching vibrations of NH, OH and aromatic CH. -1 and 1720cm -1 / 1622cm -1The absorption peaks correspond to the stretching vibrations of C=O and C=N. The characteristic absorption peak of CO appears at 1180cm -1 At 1454cm -1 , 1256cm -1 and 1096cm -1 The absorption peak at 3412 cm is the bending vibration of CH. Compared with S-CDs and G-CDs, the FT-IR spectrum of B-CDs has obvious changes. -1 The broad absorption peaks on the left and right correspond to the stretching vibration of NH / OH, 1715 cm -1 and 1611cm -1 / 1586cm -1 The absorption peak at 1457 cm corresponds to the stretching vibration of C=O and C=N. -1 and 1132cm -1 The absorption peaks correspond to the stretching vibrations of -COONa and CO. FT-IR spectra reveal that the surfaces of the three carbon dots are rich in -COOH, -NH2 and -OH functional groups, and all three have amide structures, which is consistent with the XPS results. -1 -3441cm -1 The absorption peak of the band is stronger than that of S-CDs, indicating that after 3% H2O2 treatment, S-CDs are oxidized, resulting in an increase in -OH. The absorption peak of B-CDs in NH / OH is wider and stronger than that of G-CDs, and the absorption peak of C=N becomes weaker, indicating that NaOH may have changed the surface groups of G-CDs during the formation of B-CDs, and there is Na + The presence of is equivalent to the protonation of the carbon core surface. The experimental results of FT-IR are consistent with those of XPS. Although the carbon core surfaces of the three carbon dots have similar surface groups, the slight differences in the content of different groups affect the surface states of the three carbon dots, thus giving the three carbon dots different optical properties.

[0063] 3.2 Fluorescence properties

[0064] 3.2.1 Fluorescence properties of carbon dot aqueous solutions

[0065] S-CDs, G-CDs and B-CDs were dispersed in water and their optical properties were tested. Figure 6As shown, S-CDs and G-CDs exhibit similar absorption peaks at around 222nm and 300nm, and two shoulder peaks are observed at 246nm and 289nm for B-CDs. The absorption peaks at 222nm and 246nm can be attributed to the π-π* transition of C=C in the aromatic ring, and the absorption peaks at 289nm and 300nm correspond to the n-π* transition of C=N / C=O on the surface of the carbon core. The maximum excitation wavelengths of S-CDs, G-CDs and B-CDs are 334nm, 350nm and 313nm, respectively. Under the maximum excitation wavelength, the maximum emission wavelengths of S-CDs, G-CDs and B-CDs are 435nm, 507nm and 431nm, respectively. The absorption position of C=N / C=O overlaps with the maximum excitation wavelength of the three carbon dots. The experimental data verify that the luminescence center of the three CDs originates from the C=N / C=O group. Under fluorescent light, the solutions of the three carbon dots are all colorless and transparent solutions. Under 365nm ultraviolet light, the aqueous solutions of S-CDs and B-CDs show blue fluorescence, and the G-CDs solution shows green fluorescence, which is consistent with the spectral data. With the increase of the excitation wavelength, the positions of the emission peaks of the three carbon dots remain almost unchanged, and none of them are dependent on the excitation wavelength, indicating that the three CDs have a single light-emitting channel. At the optimal excitation wavelength, the liquid absolute fluorescence quantum yields of S-CDs, G-CDs and B-CDs are 0.51%, 17.89% and 38%, respectively. Figures 7 to 9 shown.

[0066] Compared with S-CDs, the quantum yield of G-CDs increased by 35 times, and the quantum yield of B-CDs increased by 75 times. This may be because S-CDs produced more emission sites on the carbon core surface after 3% H2O2 treatment. The increase in the quantum yield of B-CDs may be related to the sodium ions attached to the carbon core surface. The sodium ions can attach to the pores on the carbon core surface to form metal cation functional groups, which is a simple and efficient strategy to increase the absolute quantum yield.

[0067] 3.2.2 Solid-state fluorescence properties of carbon dots

[0068] like Fig.10 As shown, solid-state S-CDs and G-CDs exhibit two characteristic absorption peaks at about 212nm and 250-350nm, which belong to the π-π* transition of C=C in the aromatic ring and the n-π* transition of C=N / C=O on the carbon core surface, respectively. The absorption peak of B-CDs at about 212nm is attributed to the π-π* transition of C=C in the aromatic ring, and the double peak at 264nm / 294nm and the shoulder peak at about 330nm correspond to the n-π* transition of C=O / C=N on the surface of CDs. This shows that the three have a large conjugated domain structure. Fig.10As shown, under fluorescent light, S-CDs, G-CDs, and B-CDs are white powder, milky white powder, and light yellow powder, respectively. Under UV 365nm irradiation, they exhibit blue fluorescence, green fluorescence, and bright blue fluorescence, respectively. The maximum excitation wavelengths of solid-state S-CDs, G-CDs, and B-CDs are 365nm, 374nm, and 329nm, respectively. Under the maximum excitation wavelength, the maximum emission wavelengths of S-CDs, G-CDs, and B-CDs are 444nm, 495nm, and 424nm, respectively. Moreover, the three CDs have no excitation wavelength dependence in the solid state, which is consistent with the fluorescence characteristics of the liquid state.

[0069] 3.2.3 Luminescence mechanism and stability of carbon dots

[0070] In this application, the effects of quantum size effect and surface state on photoluminescence are comprehensively considered. The particle sizes of the three prepared CDs are significantly different, and structural characterization confirms that the particle size of G-CDs is reduced compared to S-CDs. According to the quantum size effect, the emission wavelength should be blue-shifted. It is reported that the surface defects produced by the oxidation of carbon dots act as capture centers for excitons, thereby producing fluorescence associated with surface states. The increase in the carboxyl content and oxidation degree on the surface of G-CDs can lead to a red shift in the emission wavelength. The change in surface state during the formation of G-CDs dominates the effect on photoluminescence. Therefore, compared with S-CDs, the wavelength of G-CDs has been red-shifted. Compared with G-CDs, the nitrogen content on the surface of B-CDs is drastically reduced, which may have dispersed the nitrogen-containing groups on the surface of the carbon core, resulting in a reduction in the particle size of B-CDs. Due to the quantum size effect, the wavelength of B-CDs is blue-shifted.

[0071] like Fig.11 As shown in the figure, the photostability of G-CDs and B-CDs was investigated. G-CDs and B-CDs were continuously irradiated under UV light (365nm) for 60 minutes, and their fluorescence intensity was detected every 10 minutes. It was found that the fluorescence intensity of the two carbon dots remained basically unchanged. Moreover, G-CDs and B-CDs were stored at room temperature for 6 months, and the fluorescence performance remained basically unchanged. This shows that the fluorescence stability of the two carbon dots is good and can be applied to the fields of WLED optoelectronic devices and latent fingerprint imaging.

[0072] 3.3 Application of G-CDs and B-CDs

[0073] 3.3.1 Preparation and characterization of LEDs

[0074] Based on the excellent luminescence properties of G-CDs and B-CDs, they are used to prepare WLED optoelectronic devices. Before making LED devices, CDs are carefully ground in an agate mortar until they are very fine. Fig.12As shown in the figure, the prepared B-CDs and G-CDs were selected as phosphors and combined with 365nm UV chips to prepare blue (B-LED) and green (G-LED) LED lights. The CIE coordinates of B-LED and G-LED were (0.21, 0.27) and (0.27, 0.50), respectively, as shown in the figure. The correlated color temperature (CCT) values ​​were 20207K and 7001K, respectively, and the color rendering index (CRI) values ​​were 68.4 and 64.9, respectively. Then commercial red phosphor was added, and by adjusting the ratio of the three phosphors and the voltage of the working device, when the mass ratio of B-CDs, G-CDs and red phosphor was 2:3:1, WLED was obtained after packaging with 365nm UV chip as substrate. When the operating voltage is 3.29V, the device displays warm white light, CCT is 5437K, CIE coordinates are (0.33, 0.35), and CRI value is 91.4. This WLED can provide a more comfortable lighting environment, reduce visual fatigue, and meet indoor lighting requirements due to its more uniform spectral distribution. Its fluorescence spectrum is as follows Fig.12 As shown in Figure c, the emission peaks around 470nm and 520nm come from B-CDs and G-CDs phosphors, respectively, and the emission peak around 605nm comes from commercial red phosphors. The fluorescence spectrum covers the entire visible light region from 380nm to 780nm, which means that the LED lighting system has the characteristics of a wide color gamut. A lighting system with a wide color gamut can restore the color of an object more realistically and provide a richer visual experience. This new type of LED lighting not only has excellent optical properties, but also has broad application prospects in the field of solid-state lighting.

[0075] 3.3.2 Latent fingerprint detection

[0076] Fingerprints were successfully detected on black cardboard and tin foil using G-CDs and B-CDs as fluorescent markers. Fig.13 As shown in the figure, the latent fingerprint images of G-CDs and B-CDs under UV 365nm ultraviolet light are displayed. The images are not only vivid and bright, but also can clearly obtain subtle details, which greatly improves the effective recognition ability of fingerprints. This remarkable advantage is mainly attributed to the nanoscale size and lipophilicity of the particles of G-CDs and B-CDs materials. The tiny size of the nanoscale particles enables them to penetrate into the subtleties of the fingerprint texture, while the lipophilicity enhances the interaction between these particles and the oil components in the fingerprint, thereby increasing the adhesion of the fluorescent nanoparticles to the fingerprint. This adhesion not only ensures the stability of the fluorescent marker during the detection process, but also makes the fingerprint image clearer and the details more prominent. In addition, as fluorescent markers, G-CDs and B-CDs have the advantages of high brightness, good selectivity and good contrast, playing a key role in fingerprint detection, greatly improving the accuracy and reliability of latent fingerprint detection.

[0077] The present application synthesized solid-state fluorescent carbon dots with adjustable optical properties by adjusting the size and surface state of carbon dots. G-CDs were successfully prepared by oxidizing S-CDs, and high-brightness B-CDs were successfully synthesized by treating G-CDs with 0.1 mol / L NaOH, realizing the regulation of fluorescence color and quantum yield. Compared with S-CDs, the quantum yield of G-CDs increased by 35 times, and the quantum yield of B-CDs increased by 75 times. The synthesized G-CDs and B-CDs have the advantages of simple and fast synthesis method, high quantum yield, good photostability, low cost, and low toxicity. They are successfully applied to the preparation of WLEDs with high color rendering index and latent fingerprint detection. The present application provides a new idea for the synthesis of solid-state fluorescent carbon dots with high quantum yield and adjustable color, and provides a new method for the development of high-performance optoelectronic devices and reliable and accurate fluorescent markers.

[0078] The embodiments described above are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, a person skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present application, and should all be included in the protection scope of the present application.

Claims

1. A method for synthesizing matrix-free blue-green dual-color solid fluorescent carbon dots, characterized in that: The following steps are involved: 1) Using 1,2,4-benzenetricarboxylic acid and urea as precursors, a microwave-assisted method was used to synthesize blue light-seeded carbon dots S-CDs; 2) The synthesized S-CDs were oxidized with 3% H2O2 to obtain green light carbon dots G-CDs; 3) G-CDs was diluted with 0.1 mol / LNaOH treatment resulted in strong blue light carbon dots B-CDs; The microwave-assisted synthesis condition is heating at medium-high power for 10 minutes; the H2O2 oxidation treatment and NaOH treatment time are both 12 hours.

2. An application of carbon dots prepared by the synthesis method of claim 1 in LED lighting, characterized in that: a) mixing the synthesized B-CDs and G-CDs with commercial red phosphor in a mass ratio of 2:3:1; b) Mix the mixed phosphor and 365 nm UV chip is combined with substrate to prepare white light LED; c) The white light LED has a color rendering index CRI of up to 91.4 and a correlated color temperature CCT of 5437 K.

3. An application of the carbon dots prepared by the synthesis method of claim 1 in latent fingerprint detection, characterized in that: The synthesized B-CDs and G-CDs were used as fluorescent markers to improve the accuracy and reliability of latent fingerprint detection.

4. A white light LED, characterized in that: The invention is prepared by the synthesis method described in claim 1 and is suitable for indoor lighting.

5. A fluorescent marker, characterized in that The invention is prepared by the synthesis method described in claim 1 and is used to improve the accuracy and reliability of latent fingerprint detection.

6. Use of the B-CDs and G-CDs obtained according to claim 1 in biological imaging, chemical sensors, fluorescent probes and information anti-counterfeiting.

Citation Information

Patent Citations

  • Phenyl ring modified graphite-like carbon nitride photocatalyst, and preparation method and application thereof

    CN106238086A

  • Preparation method of green fluorescent carbon nitride powder

    CN106833609A